Chinese investments in Iceland: Opinions and opportunities - Tung Phuong Vu 1989- (2015)
Foreign investment is the key to exchanging capital and technology, contributing to the growth of both the host country and investing country. This is considered to be a win-win situation for both parties. The bilateral relations between Iceland and China have been strengthening in recent years, especially since the completion of the first free trade agreement which marked an historical moment between the two nations. The purpose of this thesis is to seek answers to two main research questions: What are the most plausible reasons for foreign investment from China, and what is likely to be the attitude of Icelanders towards China as an investor and towards the Free Trade Agreement between Iceland and China. In order to obtain an idea about Icelandic views to China with regard to investment and trade, a survey was conducted with students of business studies at the University of Iceland. This particular sample of respondents was chosen because they tend to be more positive than others and also because being business students they are more future oriented than the general public. This thesis applies a mixed methods quantitative and qualitative approach to support the exploration. For the quantitative section, an online survey was created and sent to a group of business students in the hopes of obtaining responses. The collected data were then categorized and brought to interviews with Mr. Össur Skarphéðinsson, a former Minister for Foreign Affairs and The former Deputy Director of Pavilion at the Ministry of Foreign Affairs Mr. Sveinn K. Einarsson to gain an understanding of the underlying reasons and motivations behind Chinese investment. Amongst other topics, the thesis also illustrates various interesting aspects of trade between Iceland and China.